Gelatin/Polycaprolactone Electrospun Nanofibrous Membranes: The Effect of Composition and Physicochemical Properties on Postoperative Cardiac Adhesion - Wang, Xingang; Xiang, Li; Peng, Yongxuan; Dai, Zihao; Hu, Yuqing; Pan, Xiaoting; Zhou, Xingliang; Zhang, Hao; Feng, Bei (Frontiers in Bioengineering and Biotechnology, 2021)
Cardiovascular diseases have become a major threat to human health. The adhesion formation is an inevitable pathophysiological event after cardiac surgery. We have previously shown that gelatin/polycaprolactone (GT/PCL, mass ratio 50:50) electrospun nanofibrous membranes have high potential in preventing postoperative cardiac adhesion, but the effect of GT:PCL composition on anti-adhesion efficacy was not investigated. Herein, nanofibrous membranes with different GT:PCL mass ratios of 0:100, 30:70, 50:50, and 70:30 were prepared via electrospinning. The 70:30 membrane failed to prevent postoperative cardiac adhesion, overly high GT contents significantly deteriorated the mechanical properties, which complicated the suturing during surgery and hardly maintained the structural integrity after implantation. Unexpectedly, the 0:100 membrane (no gelatin contained) could not effectively prevent postoperative cardiac adhesion either, since its large pore size allowed the penetration of numerous inflammatory cells to elicit a severe inflammatory response. Only the GT:PCL 50:50 membrane exhibited excellent mechanical properties, good biocompatibility and effective anti-cell penetration ability, which could serve as a physical barrier to prevent postoperative cardiac adhesion and might be suitable for other biomedical applications such as wound healing, guided tissue or bone regeneration.